Perubahan Proses Pembelajaran Tatap Muka Pasca Pembelajaran Daring Pada Masa Pandemi Covid-19 Di MAN 2 Pontianak - Iwan Ramadhan; Taufan Jaya Nugraha; Eja Firmansyah; Rio Alkahfy; Rian Rian (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to find out how the impact of the Covid-19 pandemic on the face-to-face teaching and learning process in the school environment, especially at MAN 2 Pontianak, which is one of the schools that implemented an online learning system during the Covid-19 pandemic, and has restarted learning. face-to-face with the consideration that the spread of Covid-19 has decreased and the city of Pontianak is already in the yellow zone, with a learning system that follows the rules of the health protocol. The method used in this research is descriptive qualitative, using data collection techniques in this study are interviews, observation and documentation. Changes in the learning process in the school environment need to be known, especially after online learning during the pandemic is implemented. This study intends to find out the description of changes in the face-to-face learning process after online during the pandemic to find solutions to problems in the changes that occur. The solution provided is in the form of providing input and referrals about the analysis of changes in the teaching and learning process after online learning at MAN 2 Pontianak